Pengaruh Kualitas Layanan Dan Relationship Marketing Terhadap Loyalitas Nasabah Pada Bank Jatim Cabang Perak Surabaya - Feliks Anggia B.P; Nurul Eka Rachmawati; Hotman Panjaitan (Universitas 17 Agustus 1945 Surabaya, 2016)
This research talked about client loyalty in the East Java Bank of Perak Branch,Surabaya. This research was focused on the enhancement of client loyalty based on theservice quality, and relationship marketing. From the testing results on the model in thisresearch, by using random sampling, structural equation model (SEM) analysis, and theassistance of software Amos 20, on 100 respondents, it able to explain the correlationbetween service quality and relationship marketing on the client loyalty in the East JavaBank of Perak Branch, Surabaya. Results of research showed that 1) Service qualitysignificantly affects the Relationship Marketing. 2) Service quality significantly affects theclient loyalty. 3) Relationship Marketing of the East Java Bank of Perak Branch, Surabaya,significantly affects the client loyalty. 4) Service quality significantly affects the clientloyalty, indirectly through the relationship marketing of the East Java Bank of PerakBranch, Surabaya.In this research, it was found the Determination Coefficient (RÂ²) of 0.591, this case showsthat, with the maximal service, and the good relationship marketing between the bank andthe clients will encourage the client loyalty increase of 59.1%.Key words: Service Quality, Relationship Marketing, and Loyalty.